Investigation of the effectiveness of the finite-length plastic hinge model in reinforced concrete column elements - Demirbaş, Nurbanu; Şahin, Hümeyra (Nigde Omer Halisdemir University, 2026)
In this study, the effectiveness of force-based distributed plastic behavior models for modeling the nonlinear behavior of structural members is investigated. The performance of the finite-length distributed plastic behavior model (SFM), in which plastic deformations are defined only at the end regions of the element, is evaluated in terms of accuracy and computational efficiency compared to the model that is distributed throughout the length of the element (YFM). The assessment focuses on both modeling reliability and computational efficiency. Numerical models were created with reference to a reinforced concrete column specimen tested by Tanaka. In the modeling phase, it was found that SFM models, which provide a practical approach, are more usable than YFM in terms of both reliability and computational efficiency with appropriate integration section layout and material regularization.

Bu çalışmada, taşıyıcı sistem elemanlarının doğrusal olmayan davranışlarını modellemede kullanılan kuvvet tabanlı yayılı plastik davranış modellerinin etkinliği incelenmiştir. Plastik şekil değiştirmelerin yalnızca eleman uç bölgelerinde tanımlandığı sonlu uzunluklu yayılı plastik davranış modelinin (SFM), tüm eleman boyunca yayılı olan modele (YFM) göre doğruluk ve hesaplama verimliliği açısından performansı değerlendirilmiştir. Bu kapsamda, Tanaka tarafından test edilmiş bir betonarme kolon numunesi referans alınarak sayısal modeller oluşturulmuştur. Modelleme aşamasında, pratik bir yaklaşım sağlayan SFM modellerinin uygun integrasyon kesiti yerleşimi ve malzeme düzenlemesi ile hem doğruluk hem de hesaplama verimliliği açısından YFM’ye göre daha kullanılabilir olduğu görülmüştür.
Betonarme kolon elemanlarda sonlu uzunluklu plastik mafsal modelinin etkinliğinin incelenmesi
Keywords: Reinforced Concrete Buildings; Betonarme Yapılar; Numerical Modelization in Civil Engineering; İnşaat Mühendisliğinde Sayısal Modelleme